2022
DOI: 10.3389/fpsyg.2021.751406
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Piano Performance Characteristics by Deep Learning and Artificial Intelligence and Its Application in Piano Teaching

Abstract: Deep learning (DL) and artificial intelligence (AI) are jointly applied to concrete piano teaching for children to comprehensively promote modern piano teaching and improve the overall teaching quality. First, the teaching environment and the functions of the intelligent piano are expounded. Then, a piano note onset detection method is proposed based on the convolution neural network (CNN). The network can analyze the time-frequency of the input piano music signal by transforming the original time-domain wavef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…e research results show that this piano teaching mode is beneficial to teachers and students in remote areas. Li [19] found that deep learning technology and artificial intelligence technology will provide more technical support for the improvement of modern piano teaching quality. It studies note detection methods for piano teaching using convolutional neural networks.…”
Section: Related Workmentioning
confidence: 99%
“…e research results show that this piano teaching mode is beneficial to teachers and students in remote areas. Li [19] found that deep learning technology and artificial intelligence technology will provide more technical support for the improvement of modern piano teaching quality. It studies note detection methods for piano teaching using convolutional neural networks.…”
Section: Related Workmentioning
confidence: 99%
“…Smart learning can also introduce new teaching approaches to teachers and students; Ref. [4] smart learning has evaluated piano playing with processing intelligence, artificial intelligence, and a variety of music learning software. Such tools can influence the behaviors and conduct of music students.…”
Section: Introductionmentioning
confidence: 99%